Local Experimental Intracerebral Hemorrhage in Rats - Vasilevskaya, Ekaterina (Biomedicines, 2021)
(1) Background: Hemorrhagic stroke is a lethal disease, accounting for 15% of all stroke cases. However, there are very few models of stroke with a hemorrhagic etiology. Research work is devoted to studying the development of cerebrovascular disorders in rats with an intracerebral hematoma model. The aim of this study was to conduct a comprehensive short-term study, including neurological tests, biochemical blood tests, and histomorphological studies of brain structures. (2) Methods: The model was reproduced surgically by traumatizing the brain in the capsula interna area and then injecting autologous blood. Neurological deficit was assessed according to the McGrow stroke-index scale, motor activity, orientation–exploratory behavior, emotionality, and motor functions. On Day 15, after the operation, hematological and biochemical blood tests as well as histological studies of the brain were performed. (3) Results: The overall lethality of the model was 43.7%. Acute intracerebral hematoma in rats causes marked disorders of motor activity and functional impairment, as well as inflammatory processes in the nervous tissue, which persist for at least 14 days. (4) Conclusions: This model reflects the situation observed in the clinic and reproduces the main diagnostic criteria for acute disorders of cerebral circulation.